Limited-Purpose Banking—Moving from “Trust Me” to “Show Me” Banking - Chamley, Christophe; Kotlikoff, Laurence J; Polemarchakis, Herakles (American Economic Review, 2012)
There are many alleged culprits for the bank runs of 2008 and their devastating economic fallout. But proprietary information and leverage top our list. Claims of proprietary information forced financial markets to operate on trust, while providing the perfect breeding ground for fraud. And leverage permitted creditors to run at the first whiff of fraud, leveling one financial giant after another. Limited Purpose Banking (LPB), presented here, is a financial reform that sharply curtails proprietary information and eliminates leverage and, thus, the possibility of financial collapse. LPB's adoption is supported by our simple model showing how fraud can destroy finance.